2019
DOI: 10.25035/pad.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Fair and Flexible?! Explanations Can Improve Applicant Reactions Toward Asynchronous Video Interviews

Abstract: Asynchronous video interviews are used more and more for the preselection of potential job candidates. However, recent research has shown that they are less accepted by applicants than face-to-face interviews. Our study aimed to identify ways to improve perceptions of video interviews by using explanations that emphasize standardization and flexibility. Our results showed that an explanation stressing the higher level of standardization improved fairness perceptions, whereas an explanation stressing the flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 24 publications
4
42
0
1
Order By: Relevance
“…Fortunately, however, previous research on the effects of explanations ( Truxillo et al, 2009 ) suggests that explanations that provide a justification concerning the use of a selection procedure or that stress its advantages are often a suitable way to address applicants’ concerns. In line with this research, recent evidence has shown that such explanations can also improve perceptions of technology-mediated interviews ( Basch and Melchers, 2019 ).…”
Section: Discussionsupporting
confidence: 71%
“…Fortunately, however, previous research on the effects of explanations ( Truxillo et al, 2009 ) suggests that explanations that provide a justification concerning the use of a selection procedure or that stress its advantages are often a suitable way to address applicants’ concerns. In line with this research, recent evidence has shown that such explanations can also improve perceptions of technology-mediated interviews ( Basch and Melchers, 2019 ).…”
Section: Discussionsupporting
confidence: 71%
“…Thus, explanations might also be a viable option to improve applicant perceptions of these interviews and their reactions to the selection process. In line with this possibility, a recent study by Basch and Melchers ( 2019 ) indeed found that an explanation related to the larger flexibility of technology-mediated interviews can have positive effects of the perceived flexibility and ultimately on organizational attractiveness. Thus, it would be conceivable to emphasize advantages of videoconference interviews prior to the selection process in order to prevent low fairness perceptions and poor applicant reactions such as lower organizational attractiveness (Hausknecht et al, 2004 ).…”
Section: Discussionmentioning
confidence: 77%
“…Perceived Flexibility To measure perceived flexibility, we used three items from a previous study (Basch & Melchers, 2019) (e.g., "Such an interview offers great temporal and geographical flexibility to applicants", α pre = 0.81, α post = 0.72).…”
Section: Social Presence Four Items Developed and Validated Bymentioning
confidence: 99%
See 2 more Smart Citations